2016
DOI: 10.1071/wr16052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land cover on coyote abundance

Abstract: Context Throughout the world, declines in large mammalian carnivores have led to the release of smaller meso-mammalian predators. Coyotes (Canis latrans) have increased in abundance, distribution and ecological influence following the extirpation of apex predators in North America. Coyotes have had substantial influence on many ecosystems in recently colonised portions of their range, but those influences can vary across land cover types. Thus, understanding the relationship between coyote abundance and land c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
18
1
Order By: Relevance
“…For example, high‐contrast edges are commonly associated with greater predator densities (Oehler and Litvaitis ), potentially increasing fawn predation risk in these areas. Alternatively, edges may harbor fewer predators (Cherry et al ), provide alternative food resources for predators, and increase predator foraging efficiency among cover types, resulting in lower predation rates (Burroughs et al , Rohm et al , Gulsby et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, high‐contrast edges are commonly associated with greater predator densities (Oehler and Litvaitis ), potentially increasing fawn predation risk in these areas. Alternatively, edges may harbor fewer predators (Cherry et al ), provide alternative food resources for predators, and increase predator foraging efficiency among cover types, resulting in lower predation rates (Burroughs et al , Rohm et al , Gulsby et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the assumption that coyotes would affect deer linearly through time does not seem reasonable given coyote population growth, and by extension their potential to affect prey, likely varies spatially. Studies have demonstrated abundance of eastern coyotes varies with landscape composition and configuration (Kays et al 2008, Cherry et al 2017. Therefore, variation in local and regional landscape conditions likely would result in a mosaic of population growth rates and time to population stabilization.…”
Section: Use Of Time Since Coyote Arrival To Index Coyote Abundancementioning
confidence: 99%
“…Any effect of coyotes on deer likely varies spatially, independent of time since coyote arrival, because habitat selection of eastern coyotes is nonrandom (Hinton et al 2015, Stevenson et al 2018, and diets can vary substantially, even at small spatial scales (Etheredge et al 2015, Ward et al 2018. Additionally, landscape composition and configuration can influence coyote abundance (Cherry et al 2017) and their effects on fawn survival (Gulsby et al 2017, Gingery et al 2018. This variation and resultant regional trends complicate analysis of coyote effects on deer at the scale of eastern North America.…”
Section: Regional Differences In Predation Ratementioning
confidence: 99%
“…Coyotes are commonly described as habitat generalists because they can occur in most habitat types (Chamberlain et al 2000, Litvaitis andHarrison 1989), but there may still be differences in how individuals use habitat within their home range (third-order habitat selection; Johnson 1980). Habitat selection by Coyotes is typically attributed to prey or food availability (Boisjoly et al 2010, Mills andKnowlton 1991), and studies in the eastern US suggest Coyotes select for open habitat types which are assumed to provide improved foraging capabilities (Cherry et al 2016, Crête et al 2001, Hinton et al 2015, Richer et al 2002, Ward et al 2018. However, habitat selection and utilization by Coyotes can be highly variable and likely context dependent (Gosselink et al 2003, Harrison et al 1991, Parker and Maxwell 1989, Patterson and Messier 2001.…”
Section: Introductionmentioning
confidence: 99%